Pendidikan Kristen di Keresidenan Timor pada Masa Nederlandsch Zendeling Genootschap: Suatu Kajian Historis - Fransisco de Kr. Anugerah Jacob (KENOSIS: Jurnal Kajian Teologi, 2021)
This article aims to examine and analyze how Christian education was carried out in the Timor residency during the time of the Nederlansch Zendeling Genootschap. Based on the results of the discussion, it is clear that education is a key element in the pattern of NZG evangelism. Therefore, education could never be separated from evangelism. Instead, the final destination of education is the expansion of the gospel message. The seeds of the gospel were introduced to local people through education. In its journey, the education during the NZG continued to experience ups and downs. There are problems caused by internal factors, but some are caused by external conditions. Even so, the NZG consistently continues to pay attention to the running of education services. The Christian education that has been carried out by the NZG brought a big impact on the social life of the people in the Residency of Timor.AbstrakArtikel ini bertujuan untuk mengkaji dan menganalisis bagaimana jalannya pendidikan Kristen di Keresidenan Timor pada masa Nederlansch Zendeling Genootschap. Berdasarkan hasil pembahasan, nyatalah bahwa pendidikan menjadi elemen kunci dalam pola pekabaran Injil NZG. Karena itu, pendidikan tidak akan pernah bisa dilepaskan dari pekabaran Injil. Malahan, muara dari pendidikan adalah perluasan pekabaran Injil. Sebab, melalui pendidikan, benih-benih Injil mulai diperkenalkan kepada orang-orang lokal. Dalam perjalanannya, dunia pendidikan pada masa NZG terus mengalami pasang surut. Ada persoalan-persoalan yang disebabkan oleh faktor-faktor internal, namun ada juga yang disebabkan oleh kondisi eksternal. Walau begitu, NZG secara konsisten terus memberikan perhatian terhadap jalannya pelayanan pendidikan. Pendidikan Kristen yang dijalankan oleh NZG pada akhirnya membawa dampak besar terhadap kehidupan sosial masyarakat di Keresidenan Timor.Â